Assessment of the Current Status and Problems of Potable Water Supply in Damaturu Metropolis - M., Babagana; A., Abubakar; A., Muhammad; G., Ado (International Journal For Research In Health Sciences And Nursing, 2017)
Water has been viewed as the global common heritage and everyone should, albeit effectively have an inalienable social and political right to it. However, freshwater shortage has been noticed around the globe. The challenges of water supply have contributed a factor inducing conflicts in some parts of the world because the earths freshwater is diminishing due to man’s activities and climate change. In Nigeria today, the freshwater sources available to the local inhabitants are either unsafe or difficult to obtain and are severely stressed by poor management. In Damaturu the capital city of Yobe State, Nigeria, the situation is indifferent from that of the larger Nigerian scenario pointed out so far. Thus, a study was conducted to assess the current status and problem of potable supply in Damaturu Metropolis. The study discovered that, there is inadequate supply of potable water to the people of Damaturu and its environs and that the people solely depend on tube wells provided through community participation for their daily water requirement It was also discovered that despite the large number of tube wells available, water supply is still inadequate and that the people depend mainly on water vendors to get the water they require. Besides, community participation in the provision of water supply was found to be commendable though tube wells were the only source provided by the community in spite the fact that water from tube well is not completely safe for human consumption. Lack of dependable and constant power supply was found to be the main cause of shortage of water supply in Damaturu and its environs coupled with insufficient bore holes provided by the government.